THE IMPACT OF DOMESTIC SEXUAL VIOLENCE ON WOMEN’S SELF CONCEPT : NARRATIVE REVIEW - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
One of the problems that often arise in domestic life is catching up in the household (KDRT). Most of the victims of domestic violence are women. The consequences of domestic violence that can be experienced by victims include feelings of inferiority, loss of self-confidence, and self-concept. The purposed of this literature review was to find out the impact of domestic sexual violence on women's self-concept. The design used is a narrative review using the Pubmed, Sciencedirect, ProQuest and Sage journals databases. Inclusion criteria were complete free articles for the last 5 years (2017 - 2021) with Case-Control and Cross-sectional research designs, and in English. Changes in self-concept in violent women include low self-esteem, loss of self-confidence, shame, poor self-concept, feelings of helplessness, feelings of worthlessness, hopelessness, sexual self-focus, sexual self-awareness, and sexual effication. Domestic violence causes many changes to women's self-concept, so that women who experience sexual violence in the household tend to have a negative attitude.